Comparative metabolomics reveals defence‐related modification of citrinin by Penicillium citrinum within a synthetic Penicillium–Pseudomonas community. (19th December 2018) - Shi, Yutong; Pan, Chengqian; Cen, Suoyu; Fu, Leilei; Cao, Xun; Wang, Hong; Wang, Kuiwu; Wu, Bin
Summary: Co‐occurring microorganisms have been proved to influence the performance of each other by metabolic means in nature. Here we generated a synthetic fungal‐bacterial community comprising Penicillium citrinum and Pseudomonas aeruginosa employing the previously described membrane‐separated co‐culture device. By applying a newly designed molecular networking routine, new citrinin‐related metabolites induced by the fungal‐bacterial cross‐talk were unveiled in trace amounts. A mechanically cycled co‐culture setup with external pumping forces accelerating the chemically interspecies communication was then developed to boost the production of cross‐talk‐induced metabolites. Multivariate data analysis combined with molecular networking revealed the accumulation of a pair of co‐culture‐induced molecules whose productions were positively correlated to the exchange rate in the new co‐cultures, facilitating the discovery of the previously undescribed antibiotic citrinolide with a novel skeleton. This highly oxidized citrinin adduct showed significantly enhanced antibiotic property against the partner strain P. aeruginosa than its precursor citrinin, suggesting a role in the microbial competition. Thus, we propose competitive‐advantage‐oriented structural modification driven by microbial defence response mechanism in the interspecies cross‐talk might be a promising approach in the search for novel antibiotics. Besides, this study highlights the utility of MS‐based metabolomics as an effective tool in the direct biochemical analysis of the community metabolism.